Sponge community variations within two semi-submerged caves of the Ligurian Sea (Mediterranean Sea) over a half-century time span. Issue 1 (1st January 2018) - Costa, G.; Betti, F.; Nepote, E.; Cattaneo-Vietti, R.; Pansini, M.; Bavestrello, G.; Bertolino, M.
Abstract: In the last few decades, macrobenthic community structures and their species abundances have shown significant changes in the Mediterranean Sea, whose causes were attributed to anthropogenic activities and to global warming effects. The Mediterranean sponges have shown a peculiar sensitivity to these changes: the populations of some species showed significant decreases, while others, more thermophilous, increased. Therefore, sponges may be a good proxy for evaluating the effects of environmental changes. Thanks to the observations conducted by Sarà about 55 years ago, a comparative analysis of the sponge populations present within two semi-submerged caves in the Ligurian Sea was possible. The two sponge assemblages re-studied in 2016 showed an increase in terms of specific richness and a significant change in their structural aspects, since the three-dimensional growth forms were mostly replaced by two-dimensional ones, a process observed also in other littoral communities. Consequently, the sponge communities inside the semi-submerged caves may be considered poorly resilient: the massive sponges were hit by the positive thermal anomalies occurring in the Ligurian Sea in the last decade and were replaced by encrusting forms, within a possible phase of cave recolonisation.